Wanprestasi Oleh Penjual Pada Perjanjian Pengikatan Jual Beli - Evangeli, Grace Ayu beta; Zubaedah, Rahmi; Affandi, Imanudin (Legal Spirit, 2024)
Default is an act of breaking a promise must be from the seller to perform an achievement, if the implementation of the obligation is not affected by circumstances, then the seller has committed an act of breaking promise. In this case, the occurrence of what is done seller of land to a buyer who has good faith which result in a binding sale and purchase agreement that has been agreed and sight by boyh parties. So the purpose of this study is to determine the factors that cause the seller’s default on the sale and purchase binding agreement as well as the legal consequence of the default commited by the seller and how the (legal) efforts to resolves default disputes in the land sale and purchase binding agreemenat.The research method is using normative juridical research methods that are studied using a statutory research approach, literatur, papers, and books and using descriptive analysis. From the results of this study it can be conclude that the occurrence of default in the sale binding agreement made by the seller to the buyer is caused by a negligence factor in which there is an element of intentionality in the from of no good faith from the seller. There are legal consequences for the seller, namely defaulting on the sale and purchase binding agreement namely paying compensation suffered by the buyer, transferring risks, paying case cost.